Chapter La scuola media superiore a Cuba nei primi venti anni di Rivoluzione. Al servizio della collettività e dei piani economici del Partito - Bellacci, Francesco (Studies on Adult Learning and Education, 2022)
The history of the Cuban school is doubly intertwined with the history of the country's social and economic evolution since the early days of the 1956 Revolution. Arguably, the escuela media superior has been the most subjected to experiments, reforms, successes, mistakes and difficulties, but it has been recognized as having a distinct degree of quality by international bodies, such as UNESCO. This 'level' of the Cuban educational system has assumed a fundamental role over the decades, after having resolved the shortcomings of the previous school system and having been adapted on several occasions to the changes in the socio-economic policies of the communist government. In fact, it trained qualified technicians essential to the economic development of Cuba and created a mass consciousness, whose unifying element resided in the collective commitment and not in that of the individual.